Cardiology Services During The Second Year Of The Covid-19 Pandemic - Sidhi Laksono; Hillary Kusharsamita (Faculty of Medicine, University of Jember, 2022)
Cardiology services have been affected by the COVID-19 pandemic. The consequences of the disease on cardiology services have not been studied in Indonesia, especially in the second year of this pandemic, as the surge in infections is currently declining. It is necessary to quantify the impact of the COVID-19 pandemic on cardiology services to evaluate whether or not cardiac services have returned to normal during this second year of the pandemic. The basis of research used in this study is a survey using a Google Form application. The technique to determine the research subjects carried out in this study is non-random sampling with the Purposive Sampling technique.One hundred and fifty-seven subjects were included in this study, with the majority gender of men (61.1%) as a clinical cardiologist (50.3%). Data were collected from several provinces in Indonesia from Jakarta to West Nusa Tenggara, with National Cardiovascular Center Harapan Kita as a majority hospital (n=15, 9.55%). There were generally sustained reductions in all aspects of cardiology service. However, the number of outpatients who underwent cardiac device implantation procedures did not increase. Telemedicine has been applied to 52.9% in the hospital where the subject works, yet the proportion of patients receiving telemedicine are less than 25%. During the second year of the COVID-19 pandemic, cardiology services need to establish new strategies to aid people with cardiovascular disease. More research is also needed in order to improve the efficacy of telemedicine in the future. Keywords: Hospital Cardiology Service, Telemedicine, COVID-19 Pandemic